2022
DOI: 10.1155/2022/4070060
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Study of Anti-PD-1 Immunotherapy Combined with Gemcitabine Chemotherapy in Multiline Treatment of Advanced Pancreatic Cancer

Abstract: Objective. This study aimed to investigate the efficacy and safety of anti-PD-1 immunotherapy combined with gemcitabine chemotherapy in multiline treatment of advanced pancreatic cancer. Methods. A retrospective analysis was performed on the clinical data of 32 patients with advanced pancreatic cancer treated with sintilimab regimen from January 2019 to December 2021 in our hospital. All patients were followed up until death or April 2022, in the form of outpatient, in-hospital review, or telephone follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Wang et al [31] found that sintilimab combined with neoadjuvant chemotherapy in patients with advanced rectal cancer can suppress CEA levels in patients. Liu et al [32] found that combined use of sintilimab can effectively improve CEA, CA199, and CA125 levels in patients with advanced pancreatic cancer. However, there is still a lack of direct evidence at home and abroad on the impact of sintilimab on CA242 and CD168.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [31] found that sintilimab combined with neoadjuvant chemotherapy in patients with advanced rectal cancer can suppress CEA levels in patients. Liu et al [32] found that combined use of sintilimab can effectively improve CEA, CA199, and CA125 levels in patients with advanced pancreatic cancer. However, there is still a lack of direct evidence at home and abroad on the impact of sintilimab on CA242 and CD168.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%